Environmental Valuation of Raya Lati Petangis Park Using the Travel Cost Method in Paser District, East Kalimantan - Anshary, Syafruddin; Munawir, Abdillah; Nurhasanah, Nurhasanah (ASTONJADRO, 2023)
The Lati Petangis Forest Park is a forest area that was previously a mining concession area of PT BHP Kendilo Coal which has ended its operations and was later developed into a tourism area. The purpose of this study was to determine the aspects that influence the level of visits to the Lati Petangis Grand Forest Park, Paser Regency, East Kalimantan and to analyze the Willingness to Pay (WTP) value of the Lati Petangis Grand Forest Park. The method used is the Travel Cost Method and Consumer Surplus. The results of the calculation of the environmental valuation of Nature Tourism Forest Park Raya Lati Petangis, Batu Engau District, Paser Regency, East Kalimantan using the Travel Cost Method can be concluded that the average WTP value is known to be Rp. 247,959, so that the economic value of the Lati Petangis Grand Forest Park is Rp. Rp. 725,614,497.06 per year, the consumer surplus value is Rp. Rp. 1,820,671,342.3. From the regression analysis it was found that the independent variables in the form of travel costs (X1), Age (X2), Education (X3), Income Level (X4), Cleanliness Quality (X5), and Visitor Satisfaction Level (X6) have a significant effect on the economic value of Tahura Lati Petangis which can be characterized by the high number of visits.